Production of tumour necrosis factor alpha during bovine trypanosomiasis: possible correlation with severity of anaemia associated with the disease - Sileghem, M.R.; Gaidulis, L. (International Laboratory for Research on Animal Diseases, 1995)
This paper determines whether tumour necrosis factor (TNF alpha) (a cytokine that is predominantly secreted by cells of the monocyte/macrophage lineage) production is induced during bovine trypanosomiasis and wheather or not production is correlated with disease. TNF alpha titres in plasma from Boran cattle infected with T. vivax by tsetse fly transmission and of monocytes are illustrated. Data is also presented for TNF alpha mRNA expression in monocytes isolated from Trypanosoma vivax and T. Congolense infected cattle.